Analysis of behaviour biocompatible titanium alloy (Ti-6Al-7Nb) in the micro-cutting. (November 2016) - Lauro, Carlos Henrique; Ribeiro Filho, Sérgio L.M.; Brandão, Lincoln Cardoso; Davim, J. Paulo
Abstract: Among the several processes employed to manufacture components with reduced dimensions, the cutting in micro-scale is one of the most used in modern industries. Although the micro-cutting has been studied, there are still gaps about the process to be analysed. The comprehension of micro-cutting has great importance mainly in the biomedical industry, for instance, for the manufacturing of dental implants. In order to ensure patient safety, it was researched the behaviour of the Ti-6Al-7Nb titanium alloy during micro-cutting used for biomedical applications. For that, it was developed an orthogonal micro-cutting with the variation of the cutting speed, feed rate, and spindle speed. The monitoring and signals processing technique employed in this work, allowed observe the influence of the ploughing effect in the chip, cutting forces, specific cutting energy, friction coefficient, temperature, and shear plane angle.